Clinical profile of severe anemia in adolescents from a hilly terrain tertiary care hospital in north India - Dr. Pradeep Kumar; Dr. Seema Sharma; Dr. Milap Sharma; Dr. Ashish Patel (Pediatric Review: International Journal of Pediatric Research, 2018)
Introduction: Adolescence is a vulnerable period for development of anemia. Anemia in adolescence has serious implications for a wide range of outcomes. It causes reduced resistance to infection, impaired physical growth and mental development, reduced physical fitness, work capacity and school performance. Objectives: The aim of the present study was to study the clinical profile of the adolescents (10-18 years) admitted with severe anemia. Methods: A hospital based retrospective study was conducted in the Department of Pediatrics, Dr Rajendra Prasad Government Medical College Kangra, a tertiary care institute in North India, during the period from January 2015 to December 2016. The participants in our study were the adolescent patients (10-18 years) admitted with primary diagnosis of severe anemia (Hemoglobin <7gm %). The diagnosis of type of anemia was based on hematological indices and red cell morphology on peripheral smear. Results: There were 39 patients admitted with severe anemia. This constituted 1.90% of all the admissions during the study period. The mean age of the patients was 14.97 (± 1.86) years and the mean hemoglobin was 4.66 (± 1.28) gm%. There was a female preponderance with 66.67% females as against 33.33% males. Megaloblastic anemia was the most common type of anemia (52.28%) followed by iron deficiency anemia (30.77%) and dimorphic anemia (15.38%). All of the patients belonged to poor socioeconomic status and most of them (89.74%) were vegetarian. Conclusion: Although iron deficiency anemia is the most common type of anemia in India, yet in adolescents megaloblastic and dimorphic anemia should be looked for whenever the adolescents present with severe anemia especially in the setting of malnutrition and dietary inadequacy.